Nitrogen Efficiency and Nutrient Absorption by a Sorghum-Oats Forage Succession - Rasiel Restelatto; Paulo Sergio Pavinato; Laércio Ricardo Sartor; Suelen Maria Einsfeld; Fernanda Paula Baldicera (Advances in Agriculture)
Balance between nutrient uptake by the crop and the amount of applied fertilizer is desired in a production system, and this measurement can predict the nutrient use efficiency. The present study aimed to evaluate nitrogen- (N-) use and recovery efficiency and extraction of N, phosphorus (P), and potassium (K) by sorghum (Sorghum bicolor) and black oat (Avena strigosa) forages under nitrogen fertilization in three consecutive crop cultivation. The experiment was carried out at Federal Technological University of Paraná (UTFPR), Dois Vizinhos, Paraná, Brazil, in Rhodic Hapludox soil. Treatments included 0, 37.5, 75, 150, 225, 300, and 375 kg N ha−1 applied to sorghum in the summer seasons of 2010/2011 and 2011/2012, intercalated by, respectively, 0, 40, 80, 120, 160, 200, and 240 kg N ha−1 applied to black oat in the winter/2011. Forage production, N, P, and K extraction, and N recovery efficiency were determined through samplings during the crop cycle. The highest sorghum forage production and N and K extraction were under 230 to 300 kg N ha−1, which was around 190 kg N ha−1 for black oat. The values of N recovery, efficiency, and N-use physiological efficiency were higher under lower N rates for both crops. Based on this, about 150 kg N ha−1 is recommended to obtain good sorghum forage production with higher N efficiency levels, which is about 120 kg N ha−1 for black oat.